2020
DOI: 10.1111/jam.14665
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxin genes and antimicrobial resistance in Staphylococcus aureus isolated from food products in Algeria

Abstract: Aims The aim of this study was to characterize Staphylococcusaureus isolates of food origin (dairy and meat products, pastries and sandwiches) determining the carriage in enterotoxin genes and the antimicrobial resistance pheno/genotypes. Methods and results A total of 300 food samples were collected and analysed for the detection of S. aureus. The presence of enterotoxin genes was investigated by multiplex PCRs. Resistance of isolates to 11 antimicrobials was determined using disc diffusion method and molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
22
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 57 publications
9
22
3
Order By: Relevance
“…Other studies analyzed the presence of this microorganism in ready-to-eat foods in African countries, but only fragmented and incomplete information about the enterotoxigenic S. aureus and MRSA isolated from African ready-to-eat foods is available so far. Similar to our findings, Chaalal et al [31] reported an overall S. aureus prevalence of 23.8% in pastries and cooked dishes sampled from supermarkets and university cities in Western Algeria, and Titouche et al [32], in the same country of the aforementioned study, found a prevalence of 14.46% in pastries collected from several market points (in Tizi Ouzou area), while no S. aureus contamination was found by these authors in the sampled sandwiches [32]. A prevalence of 33.26% was reported in ready-to-eat meat products collected in all the provinces of South Africa [33], while in Egypt (in Benha city), a prevalence of 50.8% was reported for ready-to-eat meat products sampled from restaurants and street vendors [34], and in Nigeria (in Port Harcourt Metropolis), 100% of the analyzed street ready-to-eat meals were reported to be contaminated by S. aureus [35].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other studies analyzed the presence of this microorganism in ready-to-eat foods in African countries, but only fragmented and incomplete information about the enterotoxigenic S. aureus and MRSA isolated from African ready-to-eat foods is available so far. Similar to our findings, Chaalal et al [31] reported an overall S. aureus prevalence of 23.8% in pastries and cooked dishes sampled from supermarkets and university cities in Western Algeria, and Titouche et al [32], in the same country of the aforementioned study, found a prevalence of 14.46% in pastries collected from several market points (in Tizi Ouzou area), while no S. aureus contamination was found by these authors in the sampled sandwiches [32]. A prevalence of 33.26% was reported in ready-to-eat meat products collected in all the provinces of South Africa [33], while in Egypt (in Benha city), a prevalence of 50.8% was reported for ready-to-eat meat products sampled from restaurants and street vendors [34], and in Nigeria (in Port Harcourt Metropolis), 100% of the analyzed street ready-to-eat meals were reported to be contaminated by S. aureus [35].…”
Section: Discussionsupporting
confidence: 91%
“…As shown by these studies, the prevalence of S. aureus contamination in ready-to-eat foods may greatly vary and, as highlighted by some authors [32,36], such differences are related to several factors that include the source (e.g., street-vendors or shops) and type of samples (e.g., animal-or non-animal-derived foods), the sample size, the accuracy of the identification method (based on cultivation characteristics, biochemical tests, or molecular biology techniques), the manufacturing procedures (e.g., involving bactericidal temperatures or not), and the overall hygienic measures that are implemented during the preparation and handling of the foods. In particular, S. aureus, being a commensal bacterium present on the skin, the nose, and mucous membranes of animals and humans [28], may contaminate food especially when poor hygienic practices and conditions exist.…”
Section: Discussionmentioning
confidence: 99%
“…Chaalal et al [11] have reported a rate of 21.5% in various types of foods, including raw milk, meat, and pastries. Other studies conducted in Algeria have found a lower prevalence, with values of 4.1%−13.6% in raw milk and traditional dairy products [22][23][24], but, to the best of our knowledge, no study has examined goat milk.…”
Section: Discussionmentioning
confidence: 67%
“…[ 11 ] have reported a rate of 21.5% in various types of foods, including raw milk, meat, and pastries. Other studies conducted in Algeria have found a lower prevalence, with values of 4.1%−13.6% in raw milk and traditional dairy products [ 22 - 24 ], but, to the best of our knowledge, no study has examined goat milk. The MRSA contamination rate in our study was higher than was that of many other studies [ 15 , 25 , 26 ] but was lower than that reported by Abd El Halem[ 27 ], with a value of 37.93%.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation